A novel method to purify neutrophils enables functional analysis of zebrafish hematopoiesis. (26th October 2020) - Konno, Katsuhiro; Kulkeaw, Kasem; Sasada, Manabu; Nii, Takenobu; Kaneyuki, Ayako; Ishitani, Tohru; Arai, Fumio; Sugiyama, Daisuke
Abstract: Zebrafish is a useful model to study vertebrate hematopoiesis, but lack of antibodies to zebrafish proteins has limited purification of hematopoietic cells. Here, we purified neutrophils from larval and adult zebrafish using the lectin Phaseolus vulgaris erythroagglutinin (PHA‐E) and DRAQ5, a DNA‐staining fluorescent dye. In adult kidney marrow, we purified neutrophil‐like PHA‐E4 low DRAQ5 low cells, which neutrophil‐type granules. Specifically, at 96‐hr post‐fertilization, we sorted large‐sized cells from larvae using forward scatter and found that they consisted of PHA‐E low DRAQ5 low populations. These cells had myeloperoxidase activity, were Sudan Black B‐positive and expressed high levels of neutrophil‐specific ( csf3r and mpx ) mRNAs, all neutrophil characteristics. Using this method, we conducted functional analysis suggesting that zyxin (Zyx) plays a role in neutrophil generation in zebrafish larvae. Overall, PHA‐E and DRAQ5‐based flow cytometry serves as a tool to purify zebrafish neutrophils. Abstract : Shown are percentages (means ±  SD ) of PHA‐Elow DRAQ5low cells among total living cells obtained from three independent flow cytometric analyses.